Ethical Orientation and Personal Benefit in Insider Trading - Faradiza, Sekar Akrom; Dewanti, Ratna Listiana (Journal the Winners: Economics, Business, Management, and Information System Journal, 2012)
Most of people think insider trading is an unfair activity because the parties that involved have unequal information. In a certain condition, unequal information used in a transaction is a fraud. The BAPEPAM’s act have regulated that insider trading is illegal. Nevertheless it is not easy to bring perpetrators to the court due to some difficulties to prove. Insider trading is motivated by self attentiveness or personal advantage. However, ethical orientation can mitigate insider trading because it can mediate personal benefit. Through a survey administrated to the students, this study would like to examine how ethical orientation can prevent insider trading. Using multiple regressions, this study found that ethical orientation could not mediate the effect of personal benefit to perpetrators behavior of insider trading. Therefore, we concluded that it is important to give ethical education as soon as possible to all the people to prevent unethical behavior like insider trading.